2014
DOI: 10.1007/s10528-014-9660-y
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Overexpression of Recombinant Heteroscorpine-1 (rHS-1), a Toxin from Heterometrus laoticus Scorpion Venom: Trends for Antibacterial Application and Antivenom Production

Abstract: Heteroscorpine-1 (HS-1) was identified as a member of the scorpine family. HS-1 shows insecticidal activities, exhibiting a low median lethal dose (LD50) in mealworm (Tenebrio molitor L.) and inhibitory activities against Bacillus subtilis, Klebsiella pneumoniae, and Pseudomonas aeruginosa. In this study, a recombinant HS-1 (rHS-1) was produced by overexpression in E. coli. A large yield of product was obtained. The structure of purified rHS-1 was confirmed through mass spectrometry. Both anti-crude venom and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There are many active ingredients in Scorpion, including antimicrobial peptides Mucroporin-M1, 31 analgesic peptide BmKBTx, 32 antiepilepsy peptide AEP, 33 antitumor peptide HS-1, 34 etc. We only detected antitumor effect of Scorpion; however, it remains unclear which active ingredient has the role in inhibiting tumor EMT and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…There are many active ingredients in Scorpion, including antimicrobial peptides Mucroporin-M1, 31 analgesic peptide BmKBTx, 32 antiepilepsy peptide AEP, 33 antitumor peptide HS-1, 34 etc. We only detected antitumor effect of Scorpion; however, it remains unclear which active ingredient has the role in inhibiting tumor EMT and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Smp76 shares high sequence similarity with two scorpion venom peptides, scorpine and HS-1, that possess antibacterial activities against multiple microorganisms (Fig. 1A) (Carballar-Lejarazu et al 2008;Uawonggul et al 2014). In addition, scorpine exhibits the inhibitory activity to DENV (Carballar-Lejarazu et al 2008).…”
Section: Smp76 Inhibits Denv/zikv Rna Infection and Protein Synthesismentioning
confidence: 98%
“…Its N-terminal amino acid sequence is similar to cecropins, whereas its C-terminal region has three pairs of disulfide bridges, sharing the same CSab motif with defensins (Renaud Conde et al 2000). Sequence similarity showed that Smp76 belongs to the family of b-KTx-like scorpine from Pandinus imperator and HS-1 from Heterometrus laoticus (Renaud Conde et al 2000;Uawonggul et al 2014). Considering the high sequence similarity of Smp76 with scorpine and HS-1 ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the venom of Vaejovis mexicanus (Koch, 1836) was more effective against Gram-negative bacteria, such as P. aeruginosa including multidrug-resistant strains [28]. Certain species, such as Heterometrus laocticus, Tityus discrepans and Opistophthalmus carinatus, produce peptides with antimicrobial effects called defensins [64][65][66]; other related peptides, such as Opistoporin-1 (Opistophthalmus carinatus) and Pandinin-1 (Pandinus imperator), both with 44 amino acids, have antimicrobial activity against Gram-positive and Gram-negative bacteria, respectively [21,67].…”
Section: Peptides With Antibacterial Activity (Abps)mentioning
confidence: 99%